Corrosión en presas de ferrocemento - Montes-García, Pedro; Jimenez-Quero, V.; Caballero-Aquino, T.; Fernández-González, A. (Revista ALCONPAT, 2011)
Many communities located at the dry areas in Oaxaca, Mexico, are unable to retain the waterprecipitated during the rainy season; as a result, they face serious water shortages of this vitalliquid the dry season. One option to solve the problem is the construction of smallferrocement dams because of their low cost and simple construction method. However,because of the small thickness and the thin cover on the reinforcement, the steel canexperience corrosion caused by the action of aggressive agents. This work studied thecorrosion risk by means of an experimental program that included tests of visual inspection,carbonation and corrosion potentials. During the visual inspection, cracking, mortardelamination and iron stains were observed; these evidenced the occurrence of corrosion. Inturn, this was corroborated by the results of corrosion potentials and the carbonation tests.Based on the results, it is concluded that the studied small dams have a high risk of corrosion(ca. greater than 90%), and in some cases severe corrosion was already occurring.